Vasundhara's appraisal - Vohra, Neharika, 1966- (SAGE Knowledge. Cases., 2015)
This case describes issues arising out of matrix virtual teams. On the one hand, the protagonist of the case, Vasundhara, feels that she was unable to perform because of inadequate support from supervisors and unclear task boundaries. On the other hand, her superior, Mahesh, feels that her rating is justified given her lackadaisical attitude towards maintaining working relationships. The HR head has been approached by Vasundhara to address the issue. The case events take place in a medium-size IT services firm which has witnessed rapid growth.